Endovascular treatment for spontaneous supraceliac isolated abdominal aortic dissection is a fabulous option. (Case report). (2020) - Alhaizaey, Abdullah; Azazy, Ahmed; Khalil, Ehab; Joudat, Mohammed; Alhazmi, Barrag
Highlights: The treatment paradigm for aortic dissection is complex and dependent on acuity of presentation with clinical and anatomical considerations. Endovascular treatment of supraceliac IAADs represents a feasible and safe. The long-term outcome data suggest that endovascular repair. Abstract: Aortic dissection originates from isolated tear in the abdominal aorta is rare but potentially life or limb-threatening condition particularly if misdiagnosed. It may have a number of clinical presentations with potentially serious adverse effects and should be considered in the differential diagnosis of any patient with an acute onset of abdominal pain radiating to the back and the buttocks together with presence or absence of a pulsatile abdominal mass, signs of limb ischemia, or discernible risk factors. Surgical and endovascular treatments are two valid options for these cases according to their clinical and anatomical considerations with acceptable results. We present a quite unusual case of a spontaneous supraceliac isolated abdominal aortic dissection with contained peri-aortic hematoma and manifesting as acute persistent abdominal pain. Better illustration of the natural history of this ill-defined pathology is needed to understand and improve patient care.